2014
DOI: 10.1373/clinchem.2014.223511
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Pharmacodynamics and Pharmacogenetics along the Calcineurin Pathway in Human Lymphocytes

Abstract: BACKGROUND Although therapeutic drug monitoring has improved the clinical use of immunosuppressive drugs, there is still interpatient variability in efficacy and toxicity that pharmacodynamic monitoring may help to reduce. To select the best biomarkers of tacrolimus pharmacodynamics, we explored the strength and variability of signal transduction and the influence of polymorphisms along the calcineurin pathway. METHODS Periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Moreover, another determinant of the complex relationship between CaN activity and exposure to TAC could be SNPs in the promoter region of the catalytic subunit of CaN (e.g. PPP3CA, rs45441997), as highlighted by the work of Noceti et al [41]. Unfortunately, genetic analysis of gene involved in the pharmacodynamic pathway of TAC could not be performed in our work.…”
Section: Plos Onementioning
confidence: 92%
“…Moreover, another determinant of the complex relationship between CaN activity and exposure to TAC could be SNPs in the promoter region of the catalytic subunit of CaN (e.g. PPP3CA, rs45441997), as highlighted by the work of Noceti et al [41]. Unfortunately, genetic analysis of gene involved in the pharmacodynamic pathway of TAC could not be performed in our work.…”
Section: Plos Onementioning
confidence: 92%
“…However, no pharmacogenetic risk factors for subclinical rejection have been reported for renal transplant recipients on CsA therapy. Genetic variability in genes coding for calcineurin could alter the susceptibility for CsA as has been shown previously for tacrolimus . Polymorphisms in these genes could potentially be related to acute rejection and/or subclinical rejection .…”
Section: Introductionmentioning
confidence: 76%
“…Biomarkers may be useful as they can quantitatively reflect the effects of a given drug on its target and also predict the clinical response to a drug 25. As the quantity of genetic data grows, genotyping will increasingly yield these useful biomarkers 26…”
Section: Discussionmentioning
confidence: 99%
“…Noceti et al25 suggested a strong association between TAC pharmacodynamic parameters and polymorphisms in PPP3CA . The authors reported that, in ex vivo TAC-treated peripheral blood mononuclear cells from 35 volunteers, the PPP3CA rs45441997 variant was associated with variability in intracellular IL-2 expression in CD4 + T cells 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation